Curricular Integration as a Foundation for Clinical Reasoning Development - Barton E. Anderson; Kimberly L. Mace; Kathryn Webster Rogers; Sara Brown (Journal of Athletic Training Education and Practice, 2026)
Context Clinical reasoning, defined as the thinking and decision-making processes that underpin clinical practice, is a critical outcome of health professions education. Clinical reasoning occurs across diagnostic, therapeutic, and contextual decision-making throughout complete episodes of patient care and develops through repeated engagement with authentic clinical problems. Objective This commentary examines intentional curricular integration, specifically the concurrent teaching of examination, diagnosis, and patient management, as a structural approach to creating opportunities for clinical reasoning development. Background Curricular structures that fragment examination, diagnosis, and patient management may limit opportunities for learners to practice clinical reasoning in ways that reflect real-world clinical practice. Although instructional strategies such as case-based learning, problem-based learning, and simulation can support clinical reasoning development, their effectiveness may be influenced by how they are embedded within the broader curricular structure. Synthesis Drawing on literature from across health professions and athletic training education, we describe several feasible curricular integration models, including integrated courses, parallel course delivery, and sequenced but intentionally linked courses. These approaches provide different mechanisms for intentionally connecting examination, diagnosis, and patient management across complete episodes of care. Results Curricular integration can increase opportunities for students to engage concurrently in diagnostic, therapeutic, and contextual reasoning and clinical decision-making across complete episodes of care. Recommendations Athletic training programs should consider intentionally structuring curricula around complete episodes of care and reinforcing integrated reasoning across both didactic and clinical education experiences. Integration may be achieved through multiple approaches and does not require wholesale curricular restructuring. Conclusions By intentionally connecting examination, diagnosis, and patient management and reinforcing integrated reasoning in classroom and clinical settings, athletic training programs can increase opportunities for students to practice clinical reasoning in ways that more closely reflect real-world clinical practice.